Hepatitis A vaccine immune response 22 years after vaccination. Issue 8 (1st May 2018) - Mosites, Emily; Gounder, Prabhu; Snowball, Mary; Morris, Julie; Spradling, Philip; Nelson, Noele; Bulkow, Lisa; Bruce, Michael; McMahon, Brian
Abstract : In the United States, the incidence of hepatitis A virus (HAV) infection has been reduced through universal childhood vaccination. However, the duration of immunogenicity for the hepatitis A vaccine is not known. We report on the 22 year follow‐up time point of a cohort of Alaska children who were randomized to three different vaccine schedules: A) 0, 1, and 2 months; B) 0, 1, and 6 months; and C) 0, 1, and 12 months. Among 46 participant available for follow‐up, 40 (87%) maintained protective levels of anti‐hepatitis A antibody. These results indicate that a supplemental booster dose is not yet necessary at or before the 22‐year time point.